Sustainable offers for drying and storage of grains: Identifying perceived value for Brazilian farmers. (May 2020) - Lermen, Fernando Henrique; Ribeiro, José Luis Duarte; Echeveste, Marcia Elisa; Milani Martins, Vera Lúcia; Tinoco, Maria Auxiliadora Cannarozzo
Abstract: The grain drying and storage process currently practiced in Brazil is mostly accomplished by firewood combustion, with a high demand for natural resources, lack of safety for operators, and a high rate of residue and pollutant generation. Brazil is the third-largest producer of grains, and public policies should restrict the firewood drying method as of the year 2020. To solve this problem, a startup developed a technology to dries grains based on oxyhydrogen combustion, using only green energy and water. This study contemplates the assessment of farmers concerning perceived value attributes and willingness-to-pay of a Sustainable Product-Service System. This solution is a mix of tangible products and intangible services offered simultaneously to solve post-harvest problems. A large survey comprising 354 small, medium, and large farmers in the South region of Brazil was conducted to evaluate the value attributes allocated by farmers for their acceptance of a new technology of grain drying and quality preservation. In this survey, to assess farmers' perceptions were applied offers based on three types of Product-Service System: options of purchasing equipment with corrective maintenance services (product-oriented Product-Service System), renting equipment with corrective and preventive maintenance services (use-oriented Product-Service System), and complementing services for the management of quality, information, drying and storage of grains (result-oriented Product-Service System). The survey results allowed the establishment of the attributes deemed necessary by farmers, who revealed preference towards the purchase offer (56.5%) over the rental offer (43.5%), emphasizing the inclusion of the maintenance service. It is concluded that to implement complete service (maintenances types and process management) offers investments are still necessary to educate farmers in the use of management technologies. The best offer to delivered value to Brazilian farmers is acquired in purchase modality composed by drying machines, preventive maintenance, silo storage, and corrective maintenance. Graphical abstract: Image 1 Highlights: Greener technologies are available for more sustainable practices of grain drying and storage process in Brazil. A Sustainable Product-Service System (PSS) approach was used to seek the willingness-to-pay (WTP) of farmers to access to a new technology. A large survey was carried out on a large number of farms from South Brazil to evaluate the best offer for a new technology adoption and use (as a S-PSS case study). The large survey results allowed the establishment of the attributes deemed necessary by farmers. A more complete S-PSS offer is needed with education of farmers in the use for the management of new technologies.